Development of Public Administration and its Research in Slovenia through the Lenses of Content Analysis of the International Public Administration Review - Polonca Kovač; Tina Jukić (Central European Public Administration Review)
The development of public administration (PA) is a worldwide topic of research, considering its importance in resolving governance issues in contemporary society. Consequently, the question of PA as a scientific discipline arises at both national and broader levels. In order to explore the state of affairs in PA trends in Slovenia and its regional context, an analysis was conducted involving 78 papers published in the leading Slovenian scientific journal – the International Public Administration Review – between 2011 and 2014. Content analysis as a method applied in the research is a widely recognized approach in social sciences and in the field of PA as well. Taking into account the respective analyses of the papers in terms of predominating discipline and mainstream topics, affiliation and collaboration of authors, language, methods of research and other criteria, we examined three main guidelines of editorial policy, namely the journal’s interdisciplinary, international and practical orientation. The results reveal that PA in Slovenia is rather multidisciplinary, with a prevailing role of management (HRM in particular), law and economics (the latter even mostly monodisciplinary). International and practical aspects, on the other hand, still offer some room for improvement. In sum, to support PA’s progress and its disciplinary evolution in line with global trends and the IPAR mission, a systematic interdisciplinary and all-European approach in future theory and practice is inevitable.